Zero-, one-, two- and three-dimensional supramolecular architectures sustained by Se…O chalcogen bonding: A crystallographic survey - Tiekink, Edward R. T. * (Elsevier, 2021)
The Cambridge Structural Database was evaluated for crystals containing Se…O chalcogen bonding interactions. These secondary bonding interactions are found to operate independently of complementary intermolecular interactions in about 13% of the structures they can potentially form. This number rises significantly when more specific interactions are considered, e.g. Se…O(carbonyl) interactions occur in 50% of cases where they can potentially form. In about 55% of cases, the supramolecular assemblies sustained by Se…O(oxygen) interactions are one-dimensional architectures, with the next most prominent being zero-dimensional assemblies, at 30%